2015
DOI: 10.1183/13993003.01824-2014
|View full text |Cite
|
Sign up to set email alerts
|

Asthma phenotypes and IgE responses

Abstract: The discovery of IgE represented a major breakthrough in allergy and asthma research, whereas the clinical interest given to IgE in asthma has been blurred until the arrival of anti-IgE biotherapy. Novel facets of the complex link between IgE and asthma have been highlighted by the effect of this treatment and by basic research. In parallel, asthma phenotyping recently evolved to the concept of endotypes, relying on identified/suspected pathobiological mechanisms to phenotype patients, but has not yet clearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
166
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(191 citation statements)
references
References 158 publications
5
166
1
9
Order By: Relevance
“…In addition, allergen-mediated cross-linking of IgE antibodies bound to the high affinity IgE receptor (FcεRI) may cause the activation and degranulation of pulmonary mast cells, leading to the IgE-dependent early airway response in asthma [31]. It has been reported that airway contraction is caused by the release of various mediators, and higher IgE production is more conducive to mast cell degranulation and airway contraction [32].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, allergen-mediated cross-linking of IgE antibodies bound to the high affinity IgE receptor (FcεRI) may cause the activation and degranulation of pulmonary mast cells, leading to the IgE-dependent early airway response in asthma [31]. It has been reported that airway contraction is caused by the release of various mediators, and higher IgE production is more conducive to mast cell degranulation and airway contraction [32].…”
Section: Discussionmentioning
confidence: 99%
“…IgE has an essential role in allergic asthma [47]. Allergic patients produce IgE antibodies specific for antigens such as house dust mite and pollens, which bind to IgE-specific receptors on mast cells and basophils.…”
Section: Total Igementioning
confidence: 99%
“…Most cases of asthma are associated with atopy (defined as the production of specific immunoglobulin (Ig)E in response to common environmental allergens), and this association has led asthma to be regarded largely as an allergic disorder along with other atopic diseases. In fact, the phenotype of childhood-onset atopic asthma is solid and early sensitization is associated in some cases with severe asthma in adulthood [4]. Moreover, atopy is a prevalent feature of all the phenotypes of adult asthma, reaching a prevalence rate of 85% in high-atopy prevalence phenotypes and 66% in low-atopy prevalence ones [5].…”
Section: Introductionmentioning
confidence: 99%